Exploring the dynamics of self-efficacy, resilience, and self-management on quality of life in type 2 diabetes patients: A moderated mediation approach from a positive psychology perspective - Zheng Ting; Wang Huicai; Zakeer Kudelati; Ge Yongkang; Ayimire Alimu; Zhang Xiaotian; Qu Xingge; Li Tong (PLoS ONE, 2025)
Objectives Type 2 diabetes mellitus (T2DM) significantly deteriorates patients’ quality of life (QOL). This study examined the dynamic interplay of factors that influence QOL in patients with T2DM, utilizing concepts from positive psychology and intrinsic mechanisms, to lay the groundwork for improving patient outcomes. Improving self-management behaviors is essential for effective disease management. Methods Using a cross-sectional design, this study incorporated 408 patients with T2DM from the endocrinology department of a public hospital in Urumqi, who were selected through convenience sampling from December 29, 2023 to June 30, 2024. Data collection tools included the General Data Questionnaire, Summary of Diabetes Self-Care Activities, Self-Efficacy for Diabetes Questionnaire, Connor-Davidson Resilience Scale, and Diabetes-Specific Quality of Life Scale. Structural equation modeling and Model 15 of Hayes’ SPSS-Process program facilitated the moderated mediation analysis. Results The findings demonstrated that self-efficacy significantly enhanced the QOL (β = -0.8557, p < 0.01), with resilience serving as a partial mediator, accounting for 43.1% of this effect. Interactions between self-efficacy and self-management, and resilience and self-management, were also significant predictors of QOL (β = -0.0751, p < 0.01 and β = -0.0073, p < 0.05, respectively). Conclusion These findings introduce a novel theoretical framework for T2DM from the perspective of positive psychology, which will be beneficial for intervention development. This study underscores the importance of promoting diabetes self-management as an effective strategy to enhance QOL. Additionally, healthcare providers must focus on fostering patients’ positive psychological traits and reliable self-management behaviors.